ANALISIS EFESIENSI FAKTOR PRODUKSI USAHATANI KENTANG (Solanum tuberosum) - Siska Yulianita (Journal Of Business, Finance, and Economics (JBFE), 2022)
The data analysis method is carried out by analyzing income, analyzing profits and analyzing efficiency. This research aims to find out: 1). To find out the income of potato farmers in Barusjulu Village, Barusjahe District, Karo Regency, North Sumatra, 2). To find out the benefits of potato farmers in Barusjulu Village, Barusjahe District, Karo Regency, North Sumatra, 3). To determine the efficiency of the use of production factors for potato farmers on farmer income in Barusjulu Village, Barusjahe District, Karo Regency, North Sumatra. Considering that one of the problems to be analyzed is how the income and profits of potato farmers are, the authors determine the sample through a population limit where if the population is less than 100 people, then the total sample taken (census method) is 30 people. This is because researchers feel that this number can already represent the characteristics of existing farmers. Potato farming costs include labour, fertilizer, seeds and land. The results showed that production factors such as labor, fertilizer, seeds, and land greatly influenced the income of potato farmers, where the income level of farmers was around 1.75%, for the feasibility level of potatoes/harvest season it was said to be feasible because when compared with the UMK in the study area the income of potato farmers is greater, and it is already efficient with an efficiency level of 37.20%, where if the value is less than 50% then the cost is called efficient.